2023
DOI: 10.3389/fmicb.2023.1211793
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage strategies for overcoming host antiviral immunity

Abstract: Phages and their bacterial hosts together constitute a vast and diverse ecosystem. Facing the infection of phages, prokaryotes have evolved a wide range of antiviral mechanisms, and phages in turn have adopted multiple tactics to circumvent or subvert these mechanisms to survive. An in-depth investigation into the interaction between phages and bacteria not only provides new insight into the ancient coevolutionary conflict between them but also produces precision biotechnological tools based on anti-phage syst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 203 publications
0
14
0
Order By: Relevance
“…Whether the purpose is to assign taxonomy [74], reveal mechanisms to avoid host defenses [75], identify auxiliary metabolic genes [76], or investigate mobile reservoirs for antimicrobial resistance genes [77,78], obtaining functional gene predictions is a critical step in analyses of viral communities. However, it can be quite challenging to assign functional predictions to viral genes annotated from metagenomic environmental data due to their large sequence diversity and the undercharacterization of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Whether the purpose is to assign taxonomy [74], reveal mechanisms to avoid host defenses [75], identify auxiliary metabolic genes [76], or investigate mobile reservoirs for antimicrobial resistance genes [77,78], obtaining functional gene predictions is a critical step in analyses of viral communities. However, it can be quite challenging to assign functional predictions to viral genes annotated from metagenomic environmental data due to their large sequence diversity and the undercharacterization of viruses.…”
Section: Discussionmentioning
confidence: 99%
“…Largegenome phages such as jumbo phages are believed to have special antidefense systems 24 ; however, a synthesis method for jumbo phages has not yet been established. Although many antiphage defense systems have been discovered, systems that counteract them have been rarely reported 3 . On average, a bacterium has been reported to have at least five defense systems 2,25-28 , and phages have likely evolved the means to counteract them.…”
Section: Discussionmentioning
confidence: 99%
“…The ongoing arms race between the bacteria and phage has driven the development of an extensive array of innate and adaptive immune strategies in bacteria 3,4 , as well as counter-immune strategies in phages 1,6 . In addition to the well-known restriction-modification (RM) and CRISPR-Cas systems, over one hundred other systems have been identified that target specific phage components or disrupt key metabolic pathways in the host cell to prevent phage propagation [3][4][5]7 .…”
Section: Introductionmentioning
confidence: 99%